Estimation of damage caused by carbonation in reinforced concrete structures in Nirgua city (Gaceta Técnica, 2022)
The present investigation consisted of surveying damage to reinforced concrete structures in the city of Nirgua, Yaracuy State, Venezuela. Through a preliminary inspection in which data of statistical interest was collected, failures or present damages were identified, classified and quantified, such as: cracks, fissures, concrete detachment, steel delamination, bleeding, stains, cracks. The survey was carried out in 2 zones, zone A called Sector Aire Libre, and zone B called Sector la Flor del Encanto E.B "Miguel Ángel Granado". The selection of the number of structures to inspect was determined by probabilistic sampling, considering preliminary investigations, in which a carbonation constant of approximately 8.32 mm/year 0.5 was determined. This study made it possible to determine if carbonation has caused damage to structures through corrosion.
Keywords: carbonation; steel corrosion; steel delamination